Sweden : Selected Issues-The Role of Government. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
Sweden's quality of life, public health, and educational attainment indicators are among the best in the world. Although it is impossible to pin down the optimal size of the welfare state precisely, the government has generally agreed to have become too big by the late 1980s. Globalization is changing the context in which the Swedish model operates by limiting its tax-based financing, but it does not rule out the preservation of its key elements. This paper assesses the effectiveness and impact of the extensive and highly developed welfare state in Sweden.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet